An Intelligent MCDM performance measurement for Maritime Logistics (IMPerMaL) / Muhamad Safuan Shamshol Bahri, S.Sarifah Radiah Shariff and Nazry Yahya - Shamshol Bahri, Muhamad Safuan; Shariff, S.Sarifah Radiah; Yahya, Nazry (Bahagian Penyelidikan dan Jaringan Industri, UiTM Melaka, 2022)
One of the enormous challenges faced by the maritime logistics industry in Malaysia is related to the development of capability of personnel, in terms of manpower and expertise. Therefore, it is of utmost important to evaluate the criteria needed for personnel in maritime logistics industry and how it varies across the different levels and different countries especially in southeast Asia. As the maritime logistics industry has become a critical component in the commercial link, the need for performed talents and manpower to support the industry is a competitive advantage to the nation. The first step is identifying the criteria that can be used in evaluating the performance of port personnel. Next step is to calculate the criteria weights using the Analytical Hierarchical Process (AHP) method; by using AHP template in Microsoft Excel by Goepel (2018). The criteria weights are used in determining the performance of the port personnel and its rank. All criteria are accepted and approved by the experts and results show consistent performance with the actual performance at the selected ports within ASEAN. material. An Intelligent Multi Criteria Decision Making (MCDM) Performance Measurement For Maritime Logistics (IMPerMaL) is developed to be able to provide a system that captures the best talent in maritime logistics and be able to help the relevant organisations namely port industry to hire and maintain its best personnel not only in Malaysia but neighbouring countries.